2017
DOI: 10.1371/journal.pgen.1006896
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1254 suppresses HO-1 expression through seed region-dependent silencing and non-seed interaction with TFAP2A transcript to attenuate NSCLC growth

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs, which direct post-transcriptional gene silencing (PTGS) and function in a vast range of biological events including cancer development. Most miRNAs pair to the target sites through seed region near the 5’ end, leading to mRNA cleavage and/or translation repression. Here, we demonstrated a miRNA-induced dual regulation of heme oxygenase-1 (HO-1) via seed region and non-seed region, consequently inhibited tumor growth of NSCLC. We identified miR-1254 as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…TFAP2A has been implicated in cancer proliferation, invasion, and epithelial-to-mesenchymal transition (EMT) [ 33 , 34 ]. However, it remains unclear whether TFAP2A is involved in tumor-induced angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TFAP2A has been implicated in cancer proliferation, invasion, and epithelial-to-mesenchymal transition (EMT) [ 33 , 34 ]. However, it remains unclear whether TFAP2A is involved in tumor-induced angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that TFAP2A promotes EMT procession by regulating TGF-β signaling in cancer cells [ 33 ] and TFAP2A regulates tumor growth via hypoxia inducible factor-1a (HIF-1a) signaling in nasopharyngeal carcinoma and NSCLC [ 34 , 41 ], whereas the HIF-1a pathway has been confirmed to promote angiogenesis [ 42 ]. To validate the role of TFAP2A in anlotinib resistance, we performed TFAP2A knockdown in AR cells and found that tumor-induced angiogenesis was decreased in AR cells by TFAP2A knockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that ectopic expression of miR-1254 caused G2/M cell arrest in the SW 1088 astrocytoma cells. Earlier investigations carried out on miR-1254 have revealed that it inhibited cell migration and invasion of cancer cells [14]. For instance, miR-1254 has been reported to inhibit the migration and invasion of colorectal cancer by inhibiting PSMD10 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding the function of miR-1254 in myocardium are lacking. miR-1254 has been linked to cell apoptosis and cell cycle arrest 33 . miR-1254-1 resides within the 15 th intron of the gene cell cycle and apoptosis regulator 1 (CCAR1) on 10q21.3.…”
Section: Discussionmentioning
confidence: 99%